Idiopathic Unilateral Enlargement of the Extraocular Muscles in an Infant. Issue 6 (November 2016) - Modi, Yasha; Erickson, Benjamin; Ranadive, Isha; Pasol, Joshua; Wester, Sara; Cavuoto, Kara
Abstract : A 6-month-old boy presented with a unilateral motility deficit of the right eye in all fields of gaze. Neuroimaging revealed unilateral enlargement of the medial, lateral, and inferior rectus muscles with sparing of the tendons. An evaluation for thyroid eye disease, idiopathic orbital inflammation, myositis, inflammatory and neoplastic infiltration of the muscle, vascular anomalies, and metastatic neuroblastoma was unrevealing. Biopsy of the muscle revealed normal architecture with an absence of inflammation, infiltration, or fibrosis. A review of the literature reveals the exceptionally rare nature of this finding. While the authors cannot rule out an atypical case of congenital euthyroid eye disease, this constellation of findings is not consistent with thyroid eye disease and may represent previously described cases of idiopathic enlargement of the extraocular muscles. Abstract : The authors present a case of a 6-month-old with unilaterally enlarged extraocular muscles, ptosis, enophthalmos, and a normal muscle biopsy specimen that remained stable over the course of 1-year follow-up.